ADOPTION OF BLOCKCHAIN TECHNOLOGY IN INDIAN PUBLIC DISTRIBUTION SYSTEM CHALLENGES AND SOLUTIONS - Kartik vadia , madhavi damle (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Indian public distribution system is a process to ensure food security in the country and provide basic food grains at subsidized rates with involvement of food corporation of India, an organization set up, and run by the government of India under Food Corporations Act 1964 & National food security bill of 2013. For increased efficiencies a proposed adoption of blockchain technology in the Indian public distribution systems which can foster transparency and monitoring systems. The paper is a suggestion of solution structure for secured and transparent systems using blockchain technology. It is a concept paper and we propose a solution to manage and track efficiently the process public distribution along with the supply chain solutions, within the Indian Public Distribution System with technology enhancement using Blockchain. The Findings in the supply chain structure of the public distribution system in terms of tracking in transportation and trade booking with robust solutions for of verification and traceability. Losses and malpractices of false bookings to avoid corrupted practices with be more effective in cost-saving, with efficient delivery and reach.